Comparison of Rendement, Viscosity, and Degree of Acidity of Bone Gelatin of Bali Cattle Fed with Lamtoro at Different Extraction Temperatures - Hasma Hasma; Muhamad Ali; Dahlanuddin Dahlanuddin; Made Sriasih; Wayan Wariata; Yuny Erwanto; Rafif Umar Faruq; Tina Vidya Mariska; Nadira Husaefa (Jurnal Penelitian Pendidikan IPA, 2024)
The increase in Bali cattle bone waste due to increased slaughter has become a severe societal problem because it will pollute the environment. If Bali cattle bone waste is appropriately processed, it will produce products with high nutritional and economic value, including gelatin. This research aimed to compare the yield, viscosity, and degree of acidity (pH) of bone gelatin from Bali cattle fed with lamtoro at different extraction temperatures. The gelatin from Bali cattle bone was produced under the influence of different extraction temperatures of 50; 60; and 70o C and each was repeated 4 times. The research method used was laboratory experimental. Data were analyzed using a Completely Randomized Design (CRD). The parameters observed were yield, pH, and viscosity. The results show that different extraction temperatures (50, 60, 70o C) had a significant effect (P < 0.05) on viscosity while a very significant effect (P < 0.01) on the degree of acidity (pH) and no significant effect (P > 0.05) to the yield. It can be concluded that a higher extraction temperature (70o C) will be accompanied by an increase in gelatin yield, but the extraction temperature of 60o C showed the maximum viscosity and acidity (pH) values